Gel mesh as "brake" to slow down DNA translocation through solid-state nanopores. Issue 31 (16th July 2015) - Tang, Zhipeng; Liang, Zexi; Lu, Bo; Li, Ji; Hu, Rui; Zhao, Qing; Yu, Dapeng
Abstract : Gel is introduced into solid-state nanopore systems to slow down DNA translocation. Abstract : Agarose gel is introduced onto the cis side of silicon nitride nanopores by a simple and low-cost method to slow down the speed of DNA translocation. DNA translocation speed is slowed by roughly an order of magnitude without losing signal to noise ratio for different DNA lengths and applied voltages in gel-meshed nanopores. The existence of the gel moves the center-of-mass position of the DNA conformation further from the nanopore center, contributing to the observed slowing of translocation speed. A reduced velocity fluctuation is also noted, which is beneficial for further applications of gel-meshed nanopores. The reptation model is considered in simulation and agrees well with the experimental results.